Dynamic recovering of long running transactions - Vaz, Cátia (2021)
Most business applications rely on the notion of long running transaction as a fundamental building block. This paper presents a calculus for modelling long running transactions within the framework of the π-calculus, with support for compensation as a recovery mechanism. The underlying model of this calculus is the asynchronous polyadic π-calculus, with transaction scopes and dynamic installation of compensation processes. We add to the framework a type system which guarantees that transactions are unequivocally identified, ensuring that upon a failure the correct compensation process is invoked. Moreover, the operational semantics of the calculus ensures both installation and activation of the compensation of a transaction.